2017
DOI: 10.1111/jerd.12347
|View full text |Cite
|
Sign up to set email alerts
|

Layperson's perception of axial midline angulation in asymmetric faces

Abstract: The dental midline should be as vertically straight as possible. If a midline cant is present, however, it is more favorable to have a dental midline angulation which points in the same direction as nose and chin deviations, rather than in the opposite direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
4
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 16 publications
(35 reference statements)
3
64
4
8
Order By: Relevance
“…Silva et al, in a previous study, concluded that 3° of frontal incisal plane cant cannot be noticeable by the majority of laypeople . An angulation of 3.5° in the axial dental midline (vertical component) can be notice independently of the direction of the cant, specifically when midline was canted in the opposite direction of nose and chin deviations . There seems to be a relevant correlation between the vertical lines and the horizontal lines …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Silva et al, in a previous study, concluded that 3° of frontal incisal plane cant cannot be noticeable by the majority of laypeople . An angulation of 3.5° in the axial dental midline (vertical component) can be notice independently of the direction of the cant, specifically when midline was canted in the opposite direction of nose and chin deviations . There seems to be a relevant correlation between the vertical lines and the horizontal lines …”
Section: Discussionmentioning
confidence: 99%
“…Facial midline inclination seems to be relevant to determine the dental midline, but horizontal lines like the occlusal plane seem to be more related to the other horizontal lines like the interpupillary line and not really influenced by a nose and chin deviation. The outcomes of this study support that idea, at least from an esthetic standpoint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations